Assessment of recirculation batch mode of operation in bioelectrochemical system; a way forward for cleaner production of energy and waste treatment - Jafary, T. (Elsevier Ltd, 2017)
Upscaling bioelectrochemical systems needs a proper operational mode to integrate them to the units operating in pilot and industrial scales. This study conducted a comprehensive investigation on combining the advantages of conventional batch and continuous operational modes in form of a simple and efficient looped configuration system, while reducing the drawbacks of each. In this regard, nine various recirculation batch (RB) systems with various recirculation to reactor volume ratios and with different recirculation flow rates were thoroughly evaluated and compared to the results of batch and continuous modes of operation. Recirculation rate and volume were both effective factors on system performance. The highest power density of 38 W/m3 was achieved amongst the various studied RB systems, which showed 40 and 32 of improvement compared to batch and continuous systems respectively. Cyclic voltammetry test approved 3.6 and 2.1 times increment of oxidation peak in the optimised RB system compared to the batch and continuous systems respectively. Moreover, electrochemical impedance spectroscopy analysis showed the significant reduction of charge transfer resistance in RB system. Rather than high energy outputs, the proposed operational mode showed promising results on reducing the waste treatment duration by 12.5 and 3 times compared to the batch and continuous systems respectively while achieving the COD and pH close to the releasing requirements. © 2016 Elsevier Ltd